2009
DOI: 10.1177/1088868309343290
|View full text |Cite
|
Sign up to set email alerts
|

Transforming “Apathy Into Movement”:The Role of Prosocial Emotions in Motivating Action for Social Change

Abstract: This article explores the synergies between recent developments in the social identity of helping, and advantaged groups' prosocial emotion. The authors review the literature on the potential of guilt, sympathy, and outrage to transform advantaged groups' apathy into positive action. They place this research into a novel framework by exploring the ways these emotions shape group processes to produce action strategies that emphasize either social cohesion or social change. These prosocial emotions have a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
296
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 251 publications
(313 citation statements)
references
References 128 publications
(285 reference statements)
8
296
0
9
Order By: Relevance
“…However, how best to motivate striving toward a shared goal is yet unclear. One factor that can affect contributions is individual identification with the group Thomas, McGarty, & Mavor, 2009;Veenstra & Haslam, 2000). To explore the impact of identification, we first distinguished between the motivation to work on a shared goal because the goal appears worthwhile and the motivation to work on a shared goal because one recognizes a need for progress (Fishbach et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, how best to motivate striving toward a shared goal is yet unclear. One factor that can affect contributions is individual identification with the group Thomas, McGarty, & Mavor, 2009;Veenstra & Haslam, 2000). To explore the impact of identification, we first distinguished between the motivation to work on a shared goal because the goal appears worthwhile and the motivation to work on a shared goal because one recognizes a need for progress (Fishbach et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…McGarty, Reynolds, & Muntele, 2006;McGarty, Bliuc, Thomas, & Bongiorno, 2009;Musgrove & McGarty, 2008;Postmes, Haslam, & Swaab, 2005;Postmes, Spears, Sakhel, & deGroot, 2001;Thomas, McGarty, & Mavor, 2009a, 2009bTurner, 1991;White, Smith, Terry, Greenslade, & McKimmie, 2009). With the inclusion of social identification and norms in our understanding of the learning process, we can then draw on this social influence literature to improve the effectiveness of the ways in which we attempt to shape student approaches to learning and educational outcomes.…”
Section: Running Head: Learning Behaviour and Outcomes: The Role For mentioning
confidence: 99%
“…In a study which examined perspective taking and prejudice, it was found that participants who were encouraged to take on the perspective of an outgroup (indicating some level of priming) reported more positive attitudes towards that group when compared with a more "objective" control group (Vescio, Sechrist, & Paolucci, 2003;also Batson et al, 2002). Empathy thus seems to be an important affective, prosocial response when it comes to reducing prejudice (see Thomas, McGarty & Mavor, 2009, for a review).…”
Section: Affective Antecedents Of Prejudice: the Role Of Empathymentioning
confidence: 99%